EVALUASI DAN INVENTARISASI JEMBATAN STRUKTUR BAJA KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Sri Agustin; Nedra Neswita (Nusantara Hasana Journal, 2025)
This study aimed to evaluate the condition of three steel truss bridges in Indragiri Hulu Regency in 2023 using the Bridge Management System (BMS) and NYSDOT methods. The assessment results showed that all three bridges, namely Trio Amanah Bridge, Danau Raja Bridge, and Sei. Singgris I Bridge, were in good condition and recommended for routine maintenance every six months. This study concludes that the application of the BMS method is effective in identifying bridge conditions and planning appropriate maintenance.